Geological Perspective as Karst Geotourism Potential: A Case Study of Vientiane Province, Laos - Prananda Putra Adam; Suryantini; Idham Andri Kurniawan (Department of Geophysical Engineering, Faculty of Engineering, University of Lampung, 2024)
The Vientiane Province is located in the northern region of Laos and is primarily characterized by a karst environment. This area holds significant potential for geotourism, much of which remains largely unexplored. The blend of natural and cultural attractions makes this region appealing for visitors. Situated in the subduction zone between the Sibumasu and Indochina plates, this area gave rise to the Loei-Phetchabun volcanic belt during the Late Permian to Early Triassic periods. The interaction of these tectonic plates has resulted in a diverse array of rock types, minerals, and unique landforms. Such geological diversity is found in only a few places worldwide, emphasizing the need for conservation efforts, including the designation of this region as a geosite for ecotourism. The aim of this research is to examine the potential of karst landscapes for geotourism. Three selected geosites in the region Muang Met, Kasy, and Vang Vieng districts each have distinct characteristics that highlight different geological features, including karst environments, fault zones, spectacular rock outcrops, fossils, caves, temples, rivers, and cultural centers. We have developed guidelines for geotourism development in this area. As this geotourism study is preliminary, it is currently limited to a few locations, with other potential geotourism sites yet to be explored. To facilitate visitor access, we have created a travel route map and designated stop sites. An overview of each district, including potential challenges to geosite development, is provided in the discussion. Sustainable geotourism development in Vientiane Province is expected to have a positive impact on the local community's social and economic well-being. We hope this paper opens up new opportunities for ecotourism in Laos, potentially paving the way for the region to be recognized as a national geopark.